Návrh na zlepšení firemní kultury - Vacenovská, Jitka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce je zaměřena na popis současného stavu firemní kultury společnosti Epcos s. r. o. Práce předkládá opatření pro zkvalitnění firemní kultury. Součástí vlastní práce je návrh etického kodexu pro společnost Epcos s. r. o., návrh vize společnosti a tvorba a vyhodnocení dotazníku týkající se komunikace, která se váže k firemní kultuře.

Master’s thesis is focused on description of the present state of organization culture of the company Epcos s. r. o. The thesis produses the disposal for upgrading organization culture. Part of own work is the proposal of ethics code for company Epcos s. r. o., proposal of vision of the company, and creation and evaluation of questionnaire which refers to the communication related to the organization culture.
Proposal for the Improvement of the Company´s Culture
Keywords: Firemní kultura; normy; hodnoty; etický kodex; dotazník; komunikace; Organisational culture; standards; values; ethics code; questionnaire; communication